African Verbal Arts Online: Intermediality and 'Technauriture' - (:unkn) unknown (My University, 2021)
This article explores the space and role of diasporic African arts on the Internet. African diasporic websites are seen as framework for cultural expression and innovation and the dynamics of online and offline migrant cultural productions. The focus of the investigation is on how orality and music are 'remediated' and connoted on websites that address different publics. Cultural productions (verbal genres as well as visual genres and music) diffused by African websites such as Sankofa.nl and Tawiza.nl (respectively Ghanaian and Moroccan Amazigh/Berber diasporas in The Netherlands) remain often neglected in the studies on the Internet and migration. This article shows that verbal arts on diasporic websites participate in self-presentation and contribute to construct the migrant community’s ‘digital imagination, both on and offline. The websites’ intermediality, however, poses questions of modification and change within the verbal arts in an acute form, as well-known problems of “orality” in written transcription and broadcasting clearly apply to dimensions of intermediated orality on websites. At the same time, there are elements of innovation as websites not only integrate previous communication technologies, but also become interactive tools and creative media in their own right. While the immediacy of the performance is lost, users and website teams participate in the construction of the social meaning of the communicative event, one that is no longer the storytelling event in itself, but the emblematic reference to it in its written/video form. In such a framework, intermediated oral genres can become forms of resistance towards cultural marginalisation (Tawiza) and global homogenisation (Sankofa). Oral artists can compose and perform in an oral/literate/technological continuum, easily moving through it. We may then interpret intermediated oral genres as a new specialisation of the verbal arts/artists and their public, one which require
Keywords: African Research